PENGEMBANGAN MEDIA PEMBELAJARAN GAULL (GAME EDUKASI WORDWALL) PADA MATERI HAK DAN KEWAJIBAN KELAS V UPT SD NEGERI 065003 MEDAN LABUHAN - Elviyani; Irfan Dahnial (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
For primary school civics lessons to be engaging, children need to be able to take part. Making engaging educational game-based learning material that students can use to apply what they've learned is one way to make this happen. So, with two goals in mind, researchers created wordwall learning material. They are interested in two things: first, making a GAULL (Wordwall Educational Game) product or piece of learning media, and second, finding out whether that piece of media is legitimate from a rights and obligations standpoint. Research and development (R&D) employs the 4 D model of development proposed by Thiagarajan in this context. Researchers in this study only implemented three stages of 4D development for GAULL learning media (Wordwall Educational Game) in Theme 4, sub-theme 1,